Epithelioid Sarcoma: Opportunities for Biology-Driven Targeted Therapy - Noujaim, Jonathan; Thway, Khin; Bajwa, Zia; Bajwa, Ayeza; Maki, Robert G.; Jones, Robin L.; Keller, Charles (Frontiers in Oncology, 2015)
Epithelioid sarcoma (ES) is a soft tissue sarcoma of children and young adults for which the preferred treatment for localized disease is wide surgical resection. Medical management is to a great extent undefined, and therefore for patients with regional and distal metastases, the development of targeted therapies is greatly desired. In this review, we will summarize clinically relevant biomarkers (e.g., SMARCB1, CA125, dysadherin, and others) with respect to targeted therapeutic opportunities. We will also examine the role of EGFR, mTOR, and polykinase inhibitors (e.g., sunitinib) in the management of local and disseminated disease. Toward building a consortium of pharmaceutical, academic, and non-profit collaborators, we will discuss the state of resources for investigating ES with respect to cell line resources, tissue banks, and registries so that a roadmap can be developed toward effective biology-driven therapies.